IMPLEMENTATION OF TECHNOLOGY-BASED CLINICAL SUPERVISION TO ENHANCE TEACHER PROFESSIONALISM IN THE DIGITAL ERA - Pribadi, Fauzi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to explore the effectiveness of clinical supervision conducted by school principals in enhancing teacher professionalism. Clinical supervision is an approach that involves systematic observation, evaluation, and reflection on teachers' instructional practices, with the goal of providing constructive feedback for improvement and professional development. This research employs a qualitative method with a case study approach in several elementary and secondary schools in the [name of the region]. Data were collected through in-depth interviews, classroom observations, and analysis of relevant documents. The results of the study indicate that clinical supervision, when conducted consistently and sustainably, can improve the quality of teaching. Teachers involved in the clinical supervision process showed improvements in lesson planning, teaching techniques, and reflective abilities. Additionally, better relationships between principals and teachers were established, positively impacting the overall school climate. Teachers felt more supported and motivated to continually develop themselves professionally. The conclusion of this study is that clinical supervision is an effective tool for fostering teacher professionalism. Well-implemented clinical supervision can result in more competent and confident teachers, ultimately contributing to the enhancement of educational quality. This study recommends training for school principals in clinical supervision techniques as well as policy support that strengthens clinical supervision practices in schools